ANALYSIS OF REGIONAL BATIK MOTIF CHARACTERISTICS AS A BASIS FOR REVITALIZATION AND DEVELOPMENT OF LEARNING MODELS - Kholis, Achmad Nur; Hertati, Elvani (JURNAL IMAJINASI, 2025)
The Indonesian education system currently implements the centralized Merdeka Curriculum, which, despite its intention to provide flexibility in learning, faces significant challenges, particularly in terms of unequal access to educational infrastructure across regions. To address this issue, it is essential to develop adaptive learning models that reflect the diverse local contexts. A strategic approach involves analyzing the sociocultural characteristics of communities in various areas. Batik Nusantara, a cultural heritage rich in symbolic meaning, illustrates these regional distinctions, primarily categorized into coastal and inland batik, each representing different societal values and worldviews. Coastal batik tends to reflect openness, boldness, and external cultural influences, while inland batik is deeply rooted in philosophical and symbolic traditions. These distinctions offer valuable insights for integrating local wisdom into curriculum design. This study adopts a qualitative methodology with a descriptive approach, utilizing literature review techniques from academic journals, articles, catalogs, and other scholarly sources. The analysis of batik motifs provides a foundation for contextualized learning through Problem-Based Learning and Project-Based Learning approaches. Such models have the potential to enhance students’ cultural identity, character development, and engagement by aligning learning experiences with the realities and values of their respective communities.